Complementary split ring resonator for isolation enhancement in 5G communication antenna array - Selvaraju, Raghuraman; Jamaluddin, Mohd Haizal; Kamarudin, Muhammad Ramlee; Nasir, Jamal; Dahri, Muhammad Hashim (Electromagnetics Academy, 2018)
A square-shaped complementary split ring resonator (CSRR) filtering structure for isolation improvement is presented in this paper. The proposed research work investigates the design and development of a simple and compact CSRR structure. In order to verify the performance of the proposed filtering element and improve the isolation among the closely placed antenna elements, arrays of configured CSRR structures are implemented between two antenna elements. An array of configured CSRR elements has been integrated with the printed antenna on the top and bottom layers. The proposed filtering elements offer an enhancement in isolation by 25 dB as compared to the simple array. The entire configuration has been simulated using the Ansoft HFSS simulator. Finally, the proposed design is fabricated and experimentally validated. In the experiment, coupling suppression of -51 dB at the operating frequency is successfully achieved, resulting in a recovery of the array pattern. The proposed antenna is highly efficient, which is suitable to be utilized for 5G communication.